Faktor-Faktor yang Berhubungan dengan Open Defecation Free (ODF) di Wilayah Kerja Puskesmas Pauh - Audrey Faiza Rosa; Yuniar Lestari; Abdiana Abdiana (FORIKES, 2023)
Open defecation free (ODF) is a condition when individuals in a community defecate in healthy latrine facilities. This study aimed to determine the factors associated with ODF status in the working area of the Pauh Health Center. This study used a mix method design. In stage I (quantitative approach), the study population was all heads of families, with a sample size of 109 heads of families selected by proportional random sampling technique. Data was collected by filling out a questionnaire. In stage II (qualitative), data was collected through in-depth interviews and focus group discussions. The results of the quantitative research showed that the dominance of each variable was: non-ODF status = 51.4%, poor knowledge = 33%, negative attitude = 47.7%, not having a latrine = 21%, the role of the head of the family is less supportive = 45 %, and the role of health workers was less supportive = 56.9%. The results of the bivariate analysis showed that there was a relationship between knowledge, attitudes, latrine ownership and the role of the head of the family and ODF status. The results of qualitative research showed that human resources, special policies, funds, facilities and infrastructure were not supportive. Program activities were carried out using triggering and counseling methods. Pre to post triggering activities did not go well. Monitoring did not go well and evaluation was carried out during mini workshops. ODF status had not been achieved, so special policies and guidelines for program implementation are needed, establishing cooperation with various parties and increasing public awareness and participation.Keywords: open defecation free; knowledge; attitude; toilet ownership; the role of the head of the family; role of health workersABSTRAK Open defecation free (ODF) merupakan kondisi ketika individu dalam komunitas melakukan buang air besar di sarana jamban sehat. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan status ODF di wilayah kerja Puskesmas Pauh. Penelitian ini menggunakan desain mix method. Pada tahap I (pendekatan kuantitatif), populasi penelitian adalah seluruh kepala keluarga, dengan ukuran sampel 109 kepala keluarga yang dipilih dengan teknik proportional random sampling. Data dikumpulkan melalui pengisian kuesioner. Pada tahap II (kualitatif), data dikumpulkan melalui wawancara mendalam dan diskusi kelompok terarah. Hasil penelitian kuantitatif menunjukkan bahwa dominasi masing-masing variabel adalah: status tidak ODF = 51,4%, pengetahuan kurang baik = 33%, sikap negatif = 47,7%, tidak memiliki jamban = 21%, peran kepala keluarga kurang mendukung = 45%, dan peran tenaga kesehatan kurang mendukung =56,9%. Hasil analisis bivariat menunjukkan adanya hubungan antara pengetahuan, sikap, kepemilikan jamban dan peran kepala keluarga dengan status ODF. Hasil penelitian kualitatif menunjukkan bahwa sumber daya manusia, kebijakan khusus, dana, sarana dan prasarana adalah tidak mendukung. Kegiatan program dilakukan dengan metode pemicuan dan penyuluhan. Kegiatan pra hingga pasca pemicuan berjalan kurang baik. Pemantauan tidak berjalan dengan baik dan evaluasi dilakukan saat lokakarya mini. Status ODF belum tercapai, sehingga perlu kebijakan khusus beserta pedoman pelaksanaan program, menjalin kerjasama dengan berbagai pihak dan meningkatkan kesadaran serta partisipasi masyarakat.Kata kunci: open defecation free; pengetahuan; sikap; kepemilikan jamban; peran kepala keluarga; peran tenaga kesehatan